1994
DOI: 10.1002/jae.3950090102
|View full text |Cite
|
Sign up to set email alerts
|

Estimating consumer preferences using market data—an application to us automobile demand

Abstract: This paper explores the possibility of using market data to identify consumer preferences. A utility function composed of ‘homogeneous’ characteristics and goods‐specific effects is used as a basic link between the goods space and the characteristics space. The functional form for the hedonic price equation, the data requirements and issues of measurement errors for estimating demand and supply of characteristics are discussed. We illustrate the methodology by considering the US automobile demand using 1969–86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Disposable income was given the greatest weight among all the factors used in their model to predict demand, and the results showed that price was a significant factor when automobile sales were depressed. Arguea, Hsiao, and Taylor (1994) developed a demand function using the data of automobile characteristics to estimate US automobile demand from 1969 to 1986. They used leastsquares estimates to calculate price elasticity and income elasticity, and found that income has a significant influence on the car demand.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Disposable income was given the greatest weight among all the factors used in their model to predict demand, and the results showed that price was a significant factor when automobile sales were depressed. Arguea, Hsiao, and Taylor (1994) developed a demand function using the data of automobile characteristics to estimate US automobile demand from 1969 to 1986. They used leastsquares estimates to calculate price elasticity and income elasticity, and found that income has a significant influence on the car demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following Carlson and Umble (1980) and Arguea, Hsiao, and Taylor (1994), personal disposable income is thus included in this study's model. Assuming that all other factors influencing demand remain unchanged, there is a positive correlation between the demand for a product and personal disposable income.…”
Section: Wwwccsenetorg/ijefmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because low-income households cannot afford energy-efficient appliances owing to the Choice models are used frequently for appliance analyses while hedonic models are used less frequently. On the other hand, hedonic models have been used for the analysis of consumer valuations of the fuel economy (Arguea, Hsiao, and Taylor, 1994;Espey and Nair, 2005;Fan and Rubin, 2009;Fifer and Bunn, 2009;McManus, 2007). Greene (2010) conducts a literature survey of consumer valuation of the fuel economy and reports that the implicit discount rates are estimated to be higher when hedonic models are applied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several applications have already been carried out for various complex products such as housing or microcomputers, and especially the automobile (Cowling and Cubbin, 1972;Agarwal and Ratchford, 1980;Cubbin and Murfin, 1987;Goodman, 1989;Argea et al, 1994). However, this method has important limitations which renders its usage somewhat delicate on the empirical level.…”
Section: Hedonic Pricesmentioning
confidence: 99%